Moral Disengagement among University Students - Nasr, Iyad Abd Muhammad; Muhammad, Sahar Hashem (Al-Adab Journal, 2022)
The research aims to know the following:1- Disengagement of the moral link among university students.3- The relational relationship to decouple the moral link with the contradictions of self-awareness among university students.The difference in the correlational relationship between moral disengagement and contradictions in self-awareness according to the gender variable (male-female) and the stage (first-fourth).4- The extent to which the contradictions of self-awareness contribute to predicting the moral disengagement of university students.Search limits:The current research for Al-Mustansiriya University students is determined for morning studies of both sexes (male - female) and the two stages (first - and fourth) for the academic year (2019-2020). After the research community has been identified, the researcher withdraws his research sample, according to methodological and scientific methods, which can represent the community as an appropriate representation. In order for the sample to be representative of its community, the researcher relied on selecting the sample in a random, stratified, equal manner, and accordingly, a sample of (400) students was chosen from the community of Al-Mustansiriya University of (29,457) students, approximately (5%) from the research community distributed among According to the type of (200) students and (200) students, and according to the stage, the number of students in the first stage reached (200) male and female students, and (200) students from the fourth stageIn order to achieve the research objectives, the researcher had to prepare two scales to measure the research variables, so the researcher adopted a foreign scale to measure the moral disengagement of (Pandora, 2001), which was taken from (Zeldman, 2014). For the purpose of measuring moral disengagement, the researcher presented it to a group of arbitrators and stated their views By translating the scale (moral disengagement) and verifying the veracity of the translation by means of translation and reverse translation, as well as displaying the paragraphs of the scale, which consists of (32) paragraphs distributed between (4) fields, and with three alternatives (agree, hesitant, reject) with weights (3, 2, 1) In succession, and for the scale of self-perception contradictions, the researcher adopted the Scale-Selves Self-Perception Contradictions Scale for Higgins (1987), which the warrior wielded (1997). The Fakronbach method, and the data were processed statistically with the help of the statistical bag program for social sciences and the use of statistical methods, (t-test) for one sample, and (t-test) for two independent samples (z-test)), and the Pearson correlation coefficient, square Kay.